A link between historical population decline in the threatened great bustard and human expansion in Iberia: evidence from genetic and demographic data. (24th September 2013) - Horreo, Jose Luis; Palacín, Carlos; Alonso, Juan Carlos; Milá, Borja
<x xml:space="preserve">Abstract</x> Early anthropogenic impacts on the abundance and distribution of wild species are difficult to document, but can help us to understand the causes and relative importance of current declines. Genetic data can be of use in inferring historical demographic events, but the accuracy of these inferences depends on the availability and precision of demographic parameters that are difficult to obtain in the field. Here, we use demographic data on Iberian populations of the threatened great bustard (Aves: Otis tarda), obtained from an intensive population monitoring programme over the last 20 years, to estimate critical population parameters (population size and generation time), which are then used in a Bayesian Skyline Plot (BSP) analysis of mitochondrial DNA sequence data to assess changes in population size over the last several thousand years. BSP showed a sudden and sharp great bustard population decline coinciding with human expansion in Iberia, and the associated agricultural and urban development and increased hunting pressure. These results illustrate the importance of human population size as a possible ultimate cause of an environmental impact that occurred in the historical past, a fact that has often been neglected. Our results also suggest the role of human activities in driving historical population declines in great bustards, and underscore the importance of precise, long‐term field data to infer past demographic trends from parameters of extant populations. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2013, 110, 518–527.